Homage to Catalonia - Orwell, George (Vintage Classics, 2021)
Both a memoir of Orwell's experiences during the Spanish Civil War and a heartfelt tribute to those who died, Homage to Catalonia is an extraordinary first-hand record of him time on the frontline. Written with all of the depth, passion and deep human understanding that defines Orwell's writing this is incredible work of non-fiction tells of the battles that were faced by ordinary working people as they fought for both their lives and their ideologies. Although Orwell was himself near-fatally wounded he finds both bleak and comic notes in his experience which is recorded with such clarity and depth that this short work has become one of his best known.
English
Keywords: DP1-402 History of Spain; Spanish Civil War; Catalonia